Optimalisasi Ruang Terbuka Hijau Berdasarkan Distribusi Suhu Permukaan Pada Pusat Kegiatan Wilayah Di Kecamatan Luwuk Kabupaten Banggai - Dg. Mapuna, Dian Fadila U; Ardiansyah Winarta; Achsan, Andi Chaerul; Hadid, Adina Khusnudzan; Khairinrahmat (Prodi PWK Universitas Tadulako, 2025)
Urban growth in Luwuk District has resulted in public green open space (GOS) covering only 5.29 hectares or approximately 2.52% of the total urban area of 209.74 hectares. This condition contributes to a significant increase in surface temperature, which at certain times reaches extreme levels. This study aims to formulate a green open space optimization strategy based on surface temperature distribution in the regional activity center of Luwuk District. The methodology consists of four stages: (1) identifying the distribution and characteristics of GOS using GIS analysis, (2) identifying surface temperature distribution through scoring analysis, (3) analyzing GOS optimization criteria using content analysis, and (4) formulating optimization directives through data triangulation. The results indicate that the existing public GOS should be maintained with improved management supported by government funding. In addition, the use of private GOS, such as residential yards with a potential area of ±78.85 hectares (37.57%), can be optimized to increase the total GOS proportion to ±84.14 hectares or 40.11% of the total area. Additional strategies include the development of green corridors in high-density areas, the use of vertical gardens in limited spaces, and the evaluation of parking areas for planting vegetation with ecological functions. This approach offers an alternative for controlling temperature and improving urban environmental quality. Keywords: green open space, surface temperature, public GOS, private GOS, optimization, Luwuk District